Synthesis of nanocellulose/cobalt oxide composite for efficient degradation of Rhodamine B by activation of peroxymonosulfate - Khili, Faouzia; Omrani, Amel Dakhlaoui (European Journal of Chemistry, 2019)
In recent years, nanofibrous materials derived from biopolymers have attracted more interest due to their numerous applications. In our study, a simple composite of cellulose nanocrystals, and cobalt oxide nanoparticles was elaborated using sodium borohydride as a chemical reducer. It has been shown that Co3O4 nanoparticles were grown on the surface of cellulose nanocrystals. An important quantity of cobalt oxide nanoparticles was detected using ICP-OES (13.5 g contained in 100 mg of the composite). The size, the morphology and the thermal stability of the composite and the obtained nanoparticles were studied using X-ray powder diffraction, Fourier-transform infrared spectroscopy, Ultraviolet-Visible spectrophotometry, Scanning electron microscopic and Transmission electron microscopic. Our obtained material was used for the degradation of Rhodamine B and it was succeeded in degradation of Rhodamine B within very short period of time (16 min). The catalytic degradation of Rhodamine B was investigated and analyzed with UV-Visible absorption spectra.